TO WHAT EXTENT CAN HUMAN RESOUCE PROFESSIONALS ENCOURAGE AN ETHICAL CULTURE IN THIER FINANCIAL ORGANISATION IN THE UK - Chugani, Dimple (2014)
Finance is a powerful industry. Commodities that support developing economies are priced through financial trades. Markets that hold pension funds rise and fall. Carlyle, an English political commentator of the 18thcentury stated that “Power corrupts and absolute power corrupts absolutely”. It is well known that Power without responsibility could turn into tyranny, which is why regulation is needed to control the power monster. Ethical issues in the financial services sector are of concern to everyone, even those outside the industry, as we are all directly or indirectly consumers of either financial services, or products and services which rely on the financial industry for support. The industry is massive and it comprises various institutional segments such as banks, securities firms, mutual fund organizations, and investment banks, insurance companies, pension funds,mortgage lenders— any many others in the financial arena.